Autoinflation Leading to Failure of Two-Piece Ambicor Implantable Penile Prosthesis: An Outcome from a Methodical Treatment of Recalcitrant Stuttering Priapism - R. Charles Welliver; Adam N. Fonseca; Bradford L. West; Kevin T. McVary; Tobias S. Köhler (Case Reports in Urology)
Introduction. We present the case of a patient who received a two-piece Ambicor penile prosthesis for idiopathic recurrent “stuttering” priapism refractory to other treatment options. The patient returned unable to deflate the device due to an interesting anatomically induced mechanical failure. Aims. To describe the method and findings of this inflatable prosthesis failure. Results. Prosthesis failure occurred due to restrictive corporal diameter and the unique characteristics of fluid reservoir location in the two-piece inflatable prosthesis. The patient was successfully converted to a semirigid prosthesis with resolution of the pain that was due to his prosthesis autoinflation. Conclusion. Stuttering priapism remains a challenging clinical problem. Penile implantation is a reasonable long-term solution in a patient refractory to less invasive options. In patients with fibrotic corpora, a malleable device should be considered (at least temporarily) if unable to dilate comfortably to 13 mm.